Pubertal development in urban Xhosa schoolgirls - Largier, Damian Douglas Christopher (Department of Obstetrics and Gynaecology, 2017)
The present study was performed in order to update available data on puberty in South African women gathered from studies among a variety of South African population groups and to compare our findings with these previous studies in order to identify any change. In addition, the children's social environment was evaluated to see if it had any influence on the timing of puberty. This study is important because a decrease in the age of onset of the various stages of puberty would be expected as the socio-economic status of the population increases. We would expect that once socio-economic and therefore nutritional equality between different communities exists, there would be little difference between the age at which children attain puberty. An absence in the trend toward a younger onset of puberty would be a cause for concern as this would imply that there has been no improvement in living conditions from the time of the original study. A relationship has also been shown to exist between an earlier age at menarche and an increased risk of breast cancer (Pike 1983), an increased risk of coronary heart disease (Colditz 1987), shorter adult height (Shangold 1989), earlier initiation of sexual activity (Soefer 1985), earlier first pregnancy, (Sandler 1984) and larger family size (Frisch 1978). This implies that as the age at which children pass through puberty decreases, it becomes increasingly important to introduce both sexual education and the availability of contraception at a correspondingly earlier age in order to avoid the tragedies of teenage pregnancies.